Dlaczego lew ma długi ogon i sypia z otwartymi oczami? Antyczne i biblijne korzenie „Fizjologa” - Tomasi-Kapral, Elżbieta (Collectanea Philologica, 2025)
At the center of the article is the Physiologus – probably the best-known text of late antiquity and the Middle Ages after the Bible – and the descriptions of animals presented there. The depictions of the individual animals are based on the idea that, in addition to the external characteristics of an animal, they should also explain its theological significance. The animals and their characteristics should also convey a moral lesson to the reader and appear exemplary and worthy of imitation in their eyes. This article will now examine the question of how allegorical representations of animals as an interpretation of the world illustrate the logic of divine creation. Selected examples are used to show the way in which the author, inspired by the pre-Christian and Christian tradition, designs the animal images, and interpretative models are analyzed that go beyond the usual equations and often bring to light multifaceted and unexpected meanings.